The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.jtho.2018.10.101
|View full text |Cite
|
Sign up to set email alerts
|

P088 Distribution of Different HER2 Mutations and Their Impact on Clinical Responses to Afatinib in HER2-Mutant Lung Cancer

Abstract: few large-scale studies revealed the clear correlation between age, tumor nodes metastases (TNM) staging and morbidity in this rare population. Method: The age of ALK-positive lung cancer at initial diagnosis were compared between various TNM stages. Clinical characteristics, morbidity and prognosis were analyzed stratified by different age groups. Results: Of 411 patients, the younger group showed more frequent T3/4 stage (P ¼ 0.014), more frequent lymph nodes metastasis (P ¼ 0.011) and more frequent distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Even considering the EGFR mutation, the PFS was much longer than the results of previous LUXlung trials [18,19]. Previously, Fang et al [20] showed a divergent therapeutic benefit from afatinib according to mutation type of HER2-altered NSCLC. Patients with G776delinsVC and G778_P780dup derive the greatest benefit from afatinib, while patients with A775_G776insYVMA, co-mutations in the TP53 and PI3K/AKT/mammalian target of rapamycin (mTOR) pathway show primary resistance to afatinib [20].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Even considering the EGFR mutation, the PFS was much longer than the results of previous LUXlung trials [18,19]. Previously, Fang et al [20] showed a divergent therapeutic benefit from afatinib according to mutation type of HER2-altered NSCLC. Patients with G776delinsVC and G778_P780dup derive the greatest benefit from afatinib, while patients with A775_G776insYVMA, co-mutations in the TP53 and PI3K/AKT/mammalian target of rapamycin (mTOR) pathway show primary resistance to afatinib [20].…”
Section: Discussionmentioning
confidence: 86%
“…Previously, Fang et al [20] showed a divergent therapeutic benefit from afatinib according to mutation type of HER2-altered NSCLC. Patients with G776delinsVC and G778_P780dup derive the greatest benefit from afatinib, while patients with A775_G776insYVMA, co-mutations in the TP53 and PI3K/AKT/mammalian target of rapamycin (mTOR) pathway show primary resistance to afatinib [20]. One preclinical study reported the efficacy of afatinib for NSCLC with HER2 amplification [21].…”
Section: Discussionmentioning
confidence: 99%